Respostas
respondido por:
2
Aplicando a formula de baskara
B^2 - 4ac
4^2 - (-4). -1
16-16
0
Aplicando na formaula
-b + ou - raiz quadrada de delta sobre 2a
(+4) + raiz de 1 / 2.-(4)
4 + 0 / 2.(-4) = -1/2
4 - 0 / 2.(-4) = 4/(-8) = 1/-2
B^2 - 4ac
4^2 - (-4). -1
16-16
0
Aplicando na formaula
-b + ou - raiz quadrada de delta sobre 2a
(+4) + raiz de 1 / 2.-(4)
4 + 0 / 2.(-4) = -1/2
4 - 0 / 2.(-4) = 4/(-8) = 1/-2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás